2010
DOI: 10.1080/07448481.2010.483706
|View full text |Cite
|
Sign up to set email alerts
|

Turning 21 and the Associated Changes in Drinking and Driving After Drinking Among College Students

Abstract: Objective We examined drinking and driving after drinking before and after turning 21. Participants Participants were drawn from first time college students who were taking part in a 4-year longitudinal study of alcohol use and behavioral risks. Methods Web-based longitudinal surveys collected data on drinking and driving after drinking from August 2004 through November 2007 (n = 1817). A subset of participants (n = 224) also monitored their daily behavior during the month they turned 21 (January through M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
4
23
0
1
Order By: Relevance
“…Men drive more than women (Skurtveit et al 1995), and men use illegal drugs more frequently than women (Rossow 2002). Students aged >21 were also more likely to engage in this drugged driving behavior, a finding consistent with the literature that reveals substantial increases in drugged driving for this age group (Beck et al 2010;Fromme et al 2010).…”
Section: Discussionsupporting
confidence: 79%
“…Men drive more than women (Skurtveit et al 1995), and men use illegal drugs more frequently than women (Rossow 2002). Students aged >21 were also more likely to engage in this drugged driving behavior, a finding consistent with the literature that reveals substantial increases in drugged driving for this age group (Beck et al 2010;Fromme et al 2010).…”
Section: Discussionsupporting
confidence: 79%
“…In a comprehensive study of drinking behavior before and after turning 21, Fromme, Wetherill, and Neal (2010) found that the frequency and quantity of alcohol consumption increased from ages 18 to 21 while the quantity per drinking occasion decreased between ages 21 and 23-a finding that is consistent with earlier studies (Pederson and LaBrie 2007;Read et al 2008). Fromme, Wetherill, and Neal (2010) concluded that heavy consumption during the earlier years is consistent with pregaming and other binge styles of drinking that are more typical of underage drinkers.…”
supporting
confidence: 78%
“…Fromme, Wetherill, and Neal (2010) concluded that heavy consumption during the earlier years is consistent with pregaming and other binge styles of drinking that are more typical of underage drinkers. After students turn 21, they have easier access to alcohol and they "may not feel as compelled to 'preparty' as when they had more limited, illegal access" (25).…”
mentioning
confidence: 95%
“…H IGH-RISK DRINKING AMONG college students is often associated with negative consequences, including criminal offenses, driving after drinking, and unwanted sexual experiences (Fromme et al, 2010;Lee et al, 2011;Lefkowitz et al, 2011;Orchowski et al, 2012). Although many college students drink, there is considerable variability in how students experience alcohol-related problems (Mallett et al, 2011a;2011b).…”
mentioning
confidence: 99%